Fenomena "Kristen Muhammadiyah": Suatu Tinjauan dari Perspektif Wawasan Dunia Kristen - Sugiharto, Ayub; Yusuf, Etni Grace Andi (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
Indonesia's pluralistic religious landscape gives rise to unique interfaith engagement phenomena, one of which is the presence of Christians in Muhammadiyah institutions without converting, known as “Muhammadiyah Christians.” This article aims to objectively describe the phenomenon and analyze it through the lens of a Christian worldview. The research uses a literature study approach and critical-theological analysis, with reference to the thoughts of Abdul Mu'ti and Fajar Riza Ul Haq, as well as the Bible-based framework of Christian theology. The research findings show that this phenomenon is not a form of religious syncretism, but rather a form of socio-relational engagement in the context of diversity. From a Christian worldview perspective, this phenomenon demands the wisdom of faith that is balanced between love and truth, as well as unwavering Christian witness in the midst of plurality. This research emphasizes the importance of healthy interfaith dialogue and contextual faith formation that is rooted in biblical truth and does not compromise the core doctrines of the Christian faith.